Kajian Teoretis tentang Suhu dan Kalor serta Perannya dalam Perpindahan Energi - Tsaniyyah, Fatimah Robiatus (Maliki Interdisciplinary Journal, 2026)
Temperature and heat are fundamental concepts in thermal physics that play an important role in understanding energy transfer phenomena. Temperature represents the average kinetic energy of particles in a system, while heat is a form of energy transferred due to a temperature difference. This article aims to theoretically examine the concepts of temperature and heat and their roles in energy transfer processes. The method used is a literature review by analyzing relevant scientific sources, including physics textbooks and journal articles. The discussion focuses on the fundamental distinction between temperature and heat, their measurement units and instruments, and the mechanisms of heat transfer, namely conduction, convection, and radiation. The results of this study indicate that a proper understanding of temperature and heat is essential for explaining natural phenomena and their applications in everyday life, such as phase changes of matter and thermal systems. In conclusion, this theoretical review emphasizes that temperature and heat play a crucial role in energy transfer and form the basis of thermodynamics.